Literature as a means of augmenting writing skills - Al-Alami, Suhair (Opción, 2019)
Highlighting the contribution literature can make in relation to promoting students’ writing skills, the author of this paper designed a literature-based course for study purposes. The statistical tests conducted for the purpose of the study revealed that the experimental group students’ performance on the pre-post writing test was significantly better than the control group students’ performance. In conclusion, it would be appropriate to use literature as an effective device that university instructors can utilize, to enhance the writing skills of foreign/second language learners